Pelatihan Desain Web Responsif melalui Webinar dan Workshop sebagai Upaya Peningkatan Kompetensi Digital Peserta - Zaky Yusuf Ajindra; Chantika Dian Anugrah; Muhammad Zaid Itqon; Akhmad Thauzi; Adrian Mustafa; Mirza Sutrisno; Rully Mujiastuti; Popy Meilina; Sitti Nurbaya Ambo; Jumail Jumail (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity aims to enhance participants' digital competency through responsive web design training conducted using integrated webinar and workshop methods. The background of this activity is based on the increasing need for adaptive web development skills across various devices to support digital personal branding. This activity involves university students and the general public and is conducted online utilizing modern communication platforms. The implementation method consists of preparation, implementation, and evaluation stages. In the implementation stage, participants attend webinar sessions to strengthen conceptual understanding of responsive web design principles, followed by workshop sessions that emphasize hands-on practice in website creation using HTML, CSS, and JavaScript. Evaluation is conducted through pre-tests and post-tests to measure program effectiveness. The results show a significant increase in participants' digital competency with an average score increase of 55.8%. These findings indicate that the integration of webinar and workshop methods is effective in improving participants' conceptual understanding and technical skills. This activity is expected to serve as a model for community service based on applicable and sustainable digital competency development.